ANALISIS PERBANDINGAN PERTUMBUHAN RASIO KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL - hikalmi; Irfan; mulia andirfa (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2021)
The purpose of this study is to test the growth of financial ratios between Islamic Commercial Banks and Conventional Commercial Banks. The object of this research is Islamic Commercial Banks and Conventional Commercial Banks for the period 2010-2019. The samples in this study are Islamic Commercial Banks and Conventional Commercial Banks in the period 2010-2019. The results show that there are differences between the ratio of CAR, ROA, ROE, OEOI, LDR, and NPL between Islamic Commercial Banks and Conventional Commercial Banks